Childhood Trauma, Gender Inequitable Attitudes, Alcohol Use and Multiple Sexual Partners: Correlates of Intimate Partner Violence in Northern Tanzania - Messersmith, Lisa J. (Journal of interpersonal violence, 2021)
Intimate partner violence (IPV), including physical, sexual, emotional, and economic violence, has profound immediate and long-term effects on individuals and communities worldwide. To date, few studies have focused on couples’ reporting of IPV. The aim of this article is to present the results of a survey of couples’ reporting of IPV and the individual, interpersonal, and social correlates of IPV in northern Tanzania. Four hundred fifty couples from Karatu District, Tanzania, completed a questionnaire measuring attitudes on gender norms and relations, men’s experience of childhood trauma, and men’s perpetration and women’s experience of IPV. We found high levels of acceptance and experience of IPV: 72% of men justified a husband’s perpetration of IPV, and 54% of men and 76% of women said that a woman should tolerate violence to keep her family together. The majority of women had ever experienced IPV (77.8%), and 73.6% and 69% had experienced IPV in the past 12 and 3 months, respectively. Men were significantly less likely to report that they had committed IPV: 63.6% ever, 48.9% in the past 12 months, and 46.2% in the past 3 months. Multivariate logistic regression found that younger men, men who reported gender inequitable attitudes, childhood trauma, multiple sexual partners, and alcohol use were significantly more likely to report IPV perpetration in the past 3 months. Younger women, and women with low levels of education and reported food shortages were significantly more likely to report IPV in the past 3 months. These results indicate that social and individual acceptance and justification of IPV are common. Experience of violence persists over time in many relationships. This study demonstrates the need for interventions that address individual-, interpersonal-, and community-level determinants of IPV, including attitudes regarding gender equity, exposure to violence as children and intergenerational violence, lack of education, and poverty.